Influence of third-generation cephalosporin utilization on the occurrence of ESBL-positive Klebsiella pneumoniae strains - Urbánek, Karel; Kolář, Milan; Lovečková, Yvona; Strojil, Jan; Šantavá, Lucie (Journal of clinical pharmacy and therapeutics, 2007)
BACKGROUND: Klebsiella pneumoniae belongs to important nosocomial pathogens causing mainly hospital-acquired infections. Beta-lactam antibiotics are frequently used in the treatment of infections caused by K. pneumoniae, but by their selection pressure the bacteria become resistant. Excessive use of third-generation cephalosporins is a risk factor for the occurrence and spread of ESBL-producing bacterial strains. The goal of this study was to describe the utilization of third-generation cephalosporins and to analyse their selection pressure on K. pneumoniae in the University Hospital in Olomouc. METHODS: Data on the utilization of antibiotics in the hospital were obtained for the period 1997-2005 from the computerized database and expressed in defined daily doses per 100 bed-days (DBD). The data were processed according to the ATC/DDD system. Klebsiella pneumoniae strains were isolated from clinical material obtained from hospitalized patients. RESULTS: Consumption of third-generation cephalosporins, which was 1.79 DBD in 1997, decreased to 0.93 in 1999, remained stable until 2002, and then increased to 2.40 DBD in 2005. During the 9-year period analysed, a total of 9564 strains of K. pneumoniae were isolated. The ESBL-positive K. pneumoniae strains frequency increased from 8% to 18%. CONCLUSIONS: Increasing utilization of third-generation cephalosporins was associated with a statistically and clinically significant increased incidence of ESBL-positive K. pneumoniae strains.
Keywords: Microbial Sensitivity Tests; beta-laktamová rezistence; hodnocení spotřeby léčiv; Humans; beta-Lactam Resistance; nemocnice univerzitní; Klebsiella pneumoniae; databáze faktografické; mikrobiální testy citlivosti; financování organizované; Hospitals, University; Financing, Organized; lidé; Klebsiella Infections; Cephalosporins; infekce bakteriemi rodu Klebsiella; infekce spojené se zdravotní péčí; Databases, Factual; beta-laktamasy; Retrospective Studies; Czech Republic; beta-Lactamases; retrospektivní studie; Česká republika; cefalosporiny; Drug Utilization Review; Cross Infection